2014
DOI: 10.1186/1471-2156-15-58
|View full text |Cite
|
Sign up to set email alerts
|

AMPD1 rs17602729 is associated with physical performance of sprint and power in elite Lithuanian athletes

Abstract: BackgroundThe C34T genetic polymorphism (rs17602729) in the AMPD1 gene, encoding the skeletal muscle-specific isoform of adenosine monophosphate deaminase (AMPD1), is a common polymorphism among Caucasians that can impair exercise capacity. The aim of the present study was twofold: (1) to determine the C34T AMPD1 allele/genotype frequency distributions in Lithuanian athletes (n = 204, stratified into three groups: endurance, sprint/power and mixed) and compare them with the allele/genotype frequency distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Finally, two studies reported low frequency of the mutant X allele in a group of top-level Spanish male endurance athletes (cyclists and runners, n ¼ 104) [56] and 127 Polish rowers [57] compared with controls. However, this observation was not confirmed by Ginevičien_ e et al [58], when 84 Lithuanian athletes were compared with 260 controls.…”
Section: Ampd1 Gln12 Allelementioning
confidence: 77%
See 1 more Smart Citation
“…Finally, two studies reported low frequency of the mutant X allele in a group of top-level Spanish male endurance athletes (cyclists and runners, n ¼ 104) [56] and 127 Polish rowers [57] compared with controls. However, this observation was not confirmed by Ginevičien_ e et al [58], when 84 Lithuanian athletes were compared with 260 controls.…”
Section: Ampd1 Gln12 Allelementioning
confidence: 77%
“…Indeed, Cieszczyk et al [211] have shown that Polish poweroriented athletes (n ¼ 158; short-distance runners, short-distance swimmers, and weightlifters) have a significantly lower (5.4% vs. 13.1%; P ¼ 0.0007) frequency of the AMPD1 12X allele than controls (n ¼ 160). These results were replicated in cohorts of Russian power-oriented athletes (n ¼ 305; boxing, wrestling, speed skating (500-1500 m), powerlifting, swimming (50-100 m), weightlifting; frequency of the 12X allele: 8.4% vs. 15.0%; P < 0.0001, in comparison with 499 controls) [212] and 47 Lithuanian sprint and power athletes (frequency of the 12X allele: 4.3% vs. 16.0%; P ¼ 0.039, in comparison with 260 controls) [58].…”
Section: Ampd1 Gln12 Allelementioning
confidence: 99%
“…The nonsense mutation c.34C > T (C to T transition in nucleotide 34, p.Gln12X, rs17602729) in exon 2 of the AMPD1 gene converts glutamine codon (CAA) into the premature stop codon (TAA), which results in the early interruption of protein synthesis and appears to be the main cause of AMPD deficiency [ 18 ]. Studies have shown that part of the population who express the mutant AMPD1 T-allele (2% of the Caucasian population are homozygous) are vulnerable to muscle weakness, muscular cramps, pain, and premature fatigue during exercises [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our dataset marathoners tended to have a higher proportion of individuals without this variation. Likewise, AMPD1 rs17602729 (allele G), also has been implicated in increased endurance (Ginevičienė et al 2014). We found that a higher proportion of marathoners in our dataset were only carriers of this allele (G;A genotypes).…”
Section: Resultsmentioning
confidence: 52%